Eksistensi Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Roudlotut Tholibin dalam Menanamkan Akhlak Santri di Desa Jatimakmur Songgom Brebes - Aola, Ikrimatul; Yuslam, Yuslam (Jurnal Kependidikan, 2024)
This research aims to describe the existence of Islamic madrasas in instilling morals in students in Jatimakmur Village, Songgom District, Brebes Regency. The author uses field research where researchers go directly into the field to obtain research data. The approach used is a descriptive qualitative approach to describe the existence of MDTA Roudlotut Tholibin in instilling morals in students. The data collection methods used in this research are interviews, observation and documentation. Next, the author analyzed the data using the Miles and Huberman model by reducing data, presenting the data and verifying the data. Then the data was tested for validity by triangulation and research extension. The research results show that the existence of MDTA Roudlotut Tholibin began with the thoughts of the Jatimakmur village religious leaders to advance Islamic education, especially in instilling morals. The moral material taught to the students is morals towards Allah, morals towards fellow human beings and morals towards the environment. The teaching methods used to instill morals include: the ta'lim method, habituation, training and the mujahadah method. There are 2 factors in instilling morals in students, namely factors that come from within a student and factors that come from outside the student.